Evaluating the Impact of Pharmacists in Medication Therapy Management for Chronic Diseases - Katkar, Aishwarya Mahesh; Shaikh, Raja Gulfam; Kathi, Srinivas Babu; Baisla, Shikha; Trivedi, Khushi; Lakra, Johny (Journal of Neonatal Surgery, 2025)
Background: Pharmacists-led Medication Therapy Management (MTM) services have been identified as an effective intervention for managing chronic disease. The impact of pharmacist-led MTM on clinical outcomes, healthcare utilization, patient satisfaction, and cost savings for patients with chronic conditions is evaluated in the study. Objectives: The main goal was to evaluate the impact of MTM interventions on clinical indicators ( HbA1c, blood pressure), healthcare resource utilization, and patient satisfaction in patients with chronic diseases ( diabetes and hypertension). Methods: Patients with chronic diseases who received pharmacist-led MTM interventions were the subjects of the observational study. Before the intervention, we collected clinical data and healthcare utilization rates (readmissions and emergency visits) as well as patient satisfaction scores. Descriptive statistics and paired t-tests were used to find significant changes, in data, in outcomes. Results: We found that clinical indicators improved greatly, HbA1c reduced from 8.5% to 7.3%, and blood pressure from 145/90 mmHg to 130/85 mmHg. In addition, healthcare utilization decreased due to 12 percent to 6 percent fewer hospital readmissions. Significant increases in patient satisfaction scores from 3.2 to 4.5 on a 5-point scale were seen. According to economic analysis, healthcare costs were reduced, especially medication and emergency room costs. Conclusion: In chronic disease management, pharmacist-led MTM interventions significantly improve clinical outcomes, reduce healthcare utilization, and improve patient satisfaction. These results demonstrate the value of MTM services to enhance patient care, lower healthcare costs, and enhance patient quality of life.